Implementation Of The Nasyid Method In Arabic Language Subjects At Anubaan Baan Suanmark School Bangkok Thailand - Umar, Muhammad Lutfi; Qorib, Muhammad; Setiawan, Hasrian Rudi; Hasanah, Lailatul (Yayasan Rahmat Islamiyah, 2023)
The aim of this research is to find out about the implementation of the nasyid method in Arabic subjects at Anuban Baan Suanmark School Bangkok Thailand. The type of research used in this research is field research using qualitative methods. This research is supported by significant data collection techniques, namely by observation and interviews. The objects in this research are school principals and teachers as informants in interviews. Meanwhile, in data analysis, researchers used the Miles and Huberman model which begins by reducing the data, then presenting the data and then verifying the data and presenting it in the form of a short description. The research results show that the nasyid method in Arabic language subjects is carried out in several stages of activities: 1) planning in determining strategies and learning methods. 2) implementation of learning in accordance with the stages that have been planned 3) evaluation of the strengths and weaknesses of the method.